Risk for Retinal Detachment After Phacoemulsification: A Whole-Population Study of Cataract Surgery Outcomes - Clark, Antony; Morlet, Nigel; Ng, Jonathon; Preen, D.; Semmens, James (American Medical Association, 2012)
Objectives: To estimate the long-term cumulative incidence of and risk factors for retinal detachment (RD) after phacoemulsification using linked administrative medical data. Methods: We used the Western Australian Data Linkage System to identify patients who underwent phacoemulsification in Western Australia between January 1989 and December 2001. Retinal detachment cases were those patients requiring admission for RD surgery after phacoemulsification that were validated by medical record review. Kaplan-Meier analysis was used to calculate a cumulative incidence. Cox proportional hazards regression modeling was used to determine the association between RD and risk factors, including patient demographics and operative and hospital factors. Some important risk factors, including axial length and Nd:YAG laser capsulotomy, were not examined. Results: We identified 237 RD cases following 65 055 phacoemulsification procedures, with a 10-year cumulative incidence of 0.68% (95% CI, 0.56%-0.83%). Significant risk factors were year of surgery (hazard ratio [HR], 0.43; 95% CI, 0.28-0.66 [1999-2001 compared with 1989-1993] for each 5-year period after 1985), age younger than 60 years (3.76; 2.83-5.00), male sex (1.91; 1.45-2.51), and anterior vitrectomy (27.60; 19.27-39.52). Hospital location, patient rural or remote locality, hospital cataract surgery volume, failed intraocular lens insertion, length of stay, and patient insurance status were not significantly associated with RD. Conclusions: Risk for RD after phacoemulsification has almost halved for each 5-year period since its adoption in the mid 1980s. Younger patient age and male sex at surgery significantly increased risk for RD. Phacoemulsification requiring anterior vitrectomy vastly increased risk for RD.